Comparative analysis of viral shedding in pediatric and adult subjects with central nervous system-associated enterovirus infections from 2013 to 2015 in Switzerland - Cordey, S.; Schibler, M.; L’Huillier, A.G.; Wagner, N.; Gonçalves, A.R.; Ambrosioni, J.; Asner, S.; Turin, L.; Posfay-Barbe, K.M.; Kaiser, L. (Journal of clinical virology, 2017)
Several enterovirus (EV) genotypes can result in aseptic meningitis, but their routes of access to the central nervous system remain to be elucidated and may differ between the pediatric and adult populations. To assess the pattern of viral shedding in pediatric and adult subjects with acute EV meningitis and to generate EV surveillance data for Switzerland. All pediatric and adult subjects admitted to the University Hospitals of Geneva with a diagnosis of EV meningitis between 2013 and 2015 were enrolled. A quantitative EV real-time reverse transcriptase (rRT)-PCR was performed on the cerebrospinal fluid (CSF), blood, stool, urine and respiratory specimens to assess viral shedding and provide a comparative analysis of pediatric and adult populations. EV genotyping was systematically performed. EV positivity rates differed significantly between pediatric and adult subjects; 62.5% of pediatric cases (no adult case) were EV-positive in stool and blood for subjects for whom these samples were all collected. Similarly, the EV viral load in blood was significantly higher in pediatric subjects. Blood C-reactive protein levels were lower and the number of leucocytes/mm3 in the CSF were higher in non-viremic than in viremic pediatric subjects, respectively. A greater diversity of EV genotypes was observed in pediatric cases, with a predominance of echovirus 30 in children ≥3 years old and adults. In contrast to adults, EV-disseminated infections are predominant in pediatric subjects and show different patterns of EV viral shedding. This observation may be useful for clinicians and contribute to modify current practices of patient care.